2010
DOI: 10.1021/jp101715j
|View full text |Cite
|
Sign up to set email alerts
|

Strong Kinetic Isotope Effect in the Dissociative Chemisorption of H2 on a PdO(101) Thin Film

Abstract: We investigated the dissociative chemisorption and oxidation of H 2 and D 2 on a PdO(101) thin film using temperature-programmed desorption (TPD) experiments and density functional theory (DFT) calculations. We find that the dissociation of H 2 is highly facile on PdO(101), with more than 90% of a saturated H 2 layer dissociating below 100 K. Most of the dissociated hydrogen reacts with the surface to produce H 2 O that desorbs above 350 K during TPD. Our experimental data demonstrate that H 2 dissociation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(91 citation statements)
references
References 43 publications
10
79
0
1
Order By: Relevance
“…The reaction involves H atoms and hence gives an evidence for the H 2 dissociation. The argument agrees with the report that H atoms resulting from H 2 on a PdO (1 0 1) thin film react with the surface O, leading to the formation of H 2 O [18].…”
Section: Resultssupporting
confidence: 92%
“…The reaction involves H atoms and hence gives an evidence for the H 2 dissociation. The argument agrees with the report that H atoms resulting from H 2 on a PdO (1 0 1) thin film react with the surface O, leading to the formation of H 2 O [18].…”
Section: Resultssupporting
confidence: 92%
“…[229,230] Even though this Review mainly focuses on molecular systems,w ew ill now briefly discuss atom tunneling on surfaces.H ydrogen atoms have been frequently observed to tunnel in surface processes. [231][232][233] It was shown that the motion of hydrogen on Cu(001), [234][235][236][237] Pd/Cu (111), [238,239] Ru(0001), [240] W(110), [241] and Ni(100) [242][243][244] surfaces is enhanced by tunneling at low temperatures.E ven the motion of CO on aC u(111) surface was shown by scanning tunneling microscopy (STM) to occur below 6K,w ith atemperature-independent hopping rate. [245] In the field of heterogeneous catalysis,t he CO oxidation and the dissociative H 2 Od esorption as well as the OH dissociation on various metal (111) surfaces were shown to be affected by tunneling.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The PdO(101) surface was modeled by a rectangular 4 × 1 unit cell, 172 with a corresponding 4 × 2 × 1 Monkhorst-Pack k-point mesh [21]. As 173 in our prior studies [33][34][35], the PdO(101) film was strained (a = …”
mentioning
confidence: 99%